2021
DOI: 10.1596/1813-9450-9634
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Effort: Physical Activity, Gender Roles, and Bargaining Power in an Agrarian Setting

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated the extent and econometric implications of non-classical measurement errors in self-reported survey data on a range of topics, while also documenting the accuracy, feasibility, and cost implications of adopting direct measurement tools, such as GPS technology for plot area measurement and outline capture [79][80][81][82], crop cutting for crop yield estimation [83][84][85][86], high-frequency phone survey data collection for measuring household agricultural labor inputs [87,88], DNA fingerprinting for crop variety identification [89,90], physical activity trackers (i.e. accelerometers) for informing the measurement and analysis of labor productivity, effort, and poverty [91][92][93][94], smartphone applications for time use measurement, recording social interactions between respondents and interviewers, or real-time travel patterns [95][96][97][98][99], lowcost testing kits for the rapid measurement of water quality [100], and "web scraping" for automating the collection of prices for selected internet retailers, as opposed to relying exclusively on survey operations for the Consumer Price Index (CPI) [101].…”
Section: Scaling Up the Use Of Objective Measurement Methodsmentioning
confidence: 99%
“…Research has demonstrated the extent and econometric implications of non-classical measurement errors in self-reported survey data on a range of topics, while also documenting the accuracy, feasibility, and cost implications of adopting direct measurement tools, such as GPS technology for plot area measurement and outline capture [79][80][81][82], crop cutting for crop yield estimation [83][84][85][86], high-frequency phone survey data collection for measuring household agricultural labor inputs [87,88], DNA fingerprinting for crop variety identification [89,90], physical activity trackers (i.e. accelerometers) for informing the measurement and analysis of labor productivity, effort, and poverty [91][92][93][94], smartphone applications for time use measurement, recording social interactions between respondents and interviewers, or real-time travel patterns [95][96][97][98][99], lowcost testing kits for the rapid measurement of water quality [100], and "web scraping" for automating the collection of prices for selected internet retailers, as opposed to relying exclusively on survey operations for the Consumer Price Index (CPI) [101].…”
Section: Scaling Up the Use Of Objective Measurement Methodsmentioning
confidence: 99%